Analysing the gyratory compaction design level for a dense mixture and a stone mastic asphalt - Gardete, Dinis (2012)
The achievement of a desired level of bituminous mixtures’ performance is an important issue to increase the durability of pavements and to reduce maintenance costs as well as its impacts. A decisive stage is the mixture design process, in particular the choice of bitumen content to be used. This parameter can affect all the major performance properties of the mixtures. In Portugal, the Marshall method is used for bituminous mixtures design. This is an empirical method which has some drawbacks in the design of non-traditional mixtures as well as some limitations to represent in-service conditions (for example the compaction of the mixtures). Many countries have been using a volumetric design method to overcome these drawbacks. The adoption of a more efficient design methodology can improve the durability of pavements, leading to important costs saving and environmental impact reduction throughout the pavement’s life cycle. However, there is a great experience with the use of the current mix design methods and the mixture’s in-service performance is thought to be generally adequate in most cases. Therefore, the compositions obtained with the current methods are regarded as a reference in the analysis of the volumetric design method. In this project a Portuguese typical dense graded bituminous mixture used in base and binder layers as well as a Stone Mastic Asphalt (SMA) mixture were formulated by the Marshall method and by the volumetric design method. The mixture’s volumetric properties were evaluated and compared with threshold values from available standards and other specifications. The results of the design processes are compared regarding the volumetric properties of the mixtures.